Developing the new learning environment: the changing role of the academic librarian - Levy, Philippa, Ed; Roberts, Sue, Ed (Facet Publishing, 2005)
"This key text captures and critically discusses the librarian's changing learning support role in an educational context, providing guidance and practical support. Written by acknowledged experts across a broad range of roles in the new academic environment, it challenges thinking in this area as well as offering practice-based advice." "This book is essential reading for practitioners at every level within the higher education and further education sectors, including information specialists, learning support professionals, academic liaison coordinators and subject specialists, academic service managers and heads of library and information services. It is also a valuable resource for all other professionals involved in the delivery of learning support, and for students of LIS and of education."--BOOK JACKET.